Glibenclamide dissolution test for drug release evaluation in tablets (Revista Brasileira de Ciências Farmacêuticas, 2007)
Glibenclamide (GLIB) or glyburide, a second-generation hypoglycemic agent is used per oral as tablets for the treatment of diabetes mellitus. Much variabilility in the treatment may occur because of the low drug aqueous solubility in tablets dosage forms. This work reports the comparison of several pilot formulation batches with the commercial reference drug dosage form (Daonil®, glibenclamide 5 mg per tablet, Aventis Pharma Ltda.). A feasible dissolution test, developed with no use of organic solvents or surfactants in the medium, showed to be discriminative regarding to different formulations tested. GLIB quantitation was performed by a previously validated reverse-phase high performance liquid chromatography (RP-HPLC). Among several dissolution profiles compared with that of a commercial reference, a potential for a generic candidate was evident (f1 4.04 and f2 69.35) for a proposed solid dosage formulation in the Brazilian market.